Literacy on technology: what do we know about the pre-service teachers today - Tam, Suet Yet; Noordin, Nooreen (Faculty of Educational Studies, Universiti Putra Malaysia, 2015)
New literacies, which encompass a wide range of technologically related skills is not fairly new within the Malaysian context. Technology in education, introduced in 1997 through the Smart School project, has been widely studied over the years in both within Malaysia and other developing countries that place importance on English as a second language. Given the circumstances then, in-service as well as pre-service teachers learned various information and communication technology (ICT) skills to prepare students for their future. Pre-service teachers today are comparatively more skilled in technology as they learnt these ICT skills when they were young. These pre-service teachers, known as the digital natives (Prensky, 2001) are born in the 1980s where technology and computer knowledge began. While there have been many studies done on teachers at large for their technological knowledge and usage in ESL classrooms, there are still limited studies that look specifically on this group of teachers that fit both the criteria investigated, which are to know their cognitive level towards technology and its significance towards their pedagogy in classrooms. This present study aimed to investigate the technological usage and confidence of 46 pre-service English language teachers selected randomly from a university and a teacher training college in Malaysia. As digital natives, these pre-service teachers would provide a glimpse on the applicability and transitions in using technology to carry out an English lesson in the class by future teachers.